AL-HASHADU POETRY BY AHMAD MATAR (AN ANALYSIS OF RIFFATERRE’S SEMIOTICS) - Umam, Muhammad Choirul; Sakinah, Nyimas (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2023)
The language used in poetry is different from the use of language in general. In addition being different in usage, poetry expresses a concept and something indirectly. Language in poetry becomes a sign, which semiotics can be studied to reveal the meaning contained in it. This study examines Ahmad Matar’s poetry entitled “al-Hashadu” by using Riffaterre's semiotic theory. This research is a descriptive qualitative research. The method of data collection applied a documentation by reading and recording techniques. The technique of analyzing data used the heuristic and hermeneutic reading techniques. The results showed that: 1) The heuristic reading of al-Hashadu poetry by Aḥmad Maṭar received imperfect meaning, 2) The hermeneutic reading of al-Hashadu poetry by Aḥmad Maṭar received a complete meaning structurally, 3) The matrix of al-Hashadu poetry by Aḥmad Maṭar was the resistance to colonialism. The model of the poetry is two sentences in the stanzas